2011
DOI: 10.1016/j.tvjl.2010.11.020
|View full text |Cite
|
Sign up to set email alerts
|

The influence of animals on the development of children

Abstract: a b s t r a c tThere is a widespread belief that interaction with an animal is beneficial for the development of children, and several studies (most with methodological shortcomings) have investigated the influence of (companion) animals on the social-emotional and cognitive development of children. In this article, the 1984 model of Professor Jay Belsky has been used to describe which variables influence the development of children and how the companion animal-child interaction influences these variables. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 69 publications
(81 reference statements)
0
75
0
6
Order By: Relevance
“…Research has consistently found that positive relations with animals can deeply benefit the social, emotional, cognitive and educational growth of children (Arbour, Signal, & Taylor, 2009;Endenburg & van Lith, 2011). In particular, humane education programmes (HEPs) have been shown to have multiple benefits across different groups of children and young people.…”
mentioning
confidence: 99%
“…Research has consistently found that positive relations with animals can deeply benefit the social, emotional, cognitive and educational growth of children (Arbour, Signal, & Taylor, 2009;Endenburg & van Lith, 2011). In particular, humane education programmes (HEPs) have been shown to have multiple benefits across different groups of children and young people.…”
mentioning
confidence: 99%
“…Petting or grooming the horse seems to create an emotional bond, and this does not require an ownership relationship between man and horse, as has been shown in earlier studies (Bachi, Terkel, & Teichman, 2012;Endenburg & van Lith, 2011). However, it might be relevant that the client had the same horse throughout the treatment process, as even Hauge et al, (2013) highlight in their study.…”
Section: Discussionmentioning
confidence: 55%
“…In the hospital setting, there are several studies that have examined the benefits of AAT in children, particularly in the pediatric population [8][9][10]. The reported results suggest that, after individual sessions of AAT, the patient displayed a short-term capacity to reduce the stress response and an improvement in mood [11,12].…”
Section: Introductionmentioning
confidence: 99%